Analysis of Basic Passing Technique Skills in Futsal Games at Palopo 4 Public Middle School - Prasetya, Rezha Chandra; Ahmad, Ahmad; Aliah, Husnani (Department of Physical Education, Sport, Health and Recreation, 2023)
This research is a type of descriptive research. This study aims to determine the Passing Skills in the Futsal Game of SMP Negeri 4 Palopo. This research uses descriptive quantitative research by collecting data based on real data then compiling, processing and analyzing it to get a picture of the existing problems. The population is all Futsal players at SMP Negeri 4 Palopo.All 20 players of the Palopo 4 Public Middle School futsal team were used as samples. The sampling technique uses a saturated sample. The data analysis technique used is descriptive analysis, percentage descriptive analysis. The results of the completeness level of SMP Negeri 4 Palopo students in this study showed the classification of